(untitled) (Communications in Computational Physics, 2020)
Realization of the Shan-Chen multiphase flow lattice Boltzmann model is considered in the framework of the higher-order Galilean invariant lattices. The present multiphase lattice Boltzmann model is used in two-dimensional simulation of droplet collisions at high Weber numbers. Results are found to be in a good agreement with experimental findings.